Feedback and Feedforward Control in DC/DC Boost Converter - Bilhan, Aye Kocalmis; Caliskan, Abuzer; Unal, Sencer (Ieee, 2016)
An Electrical Vehicle is a vehicle which uses a combination of Fuel Cells (FCs), Batteries and Supercapacitors (SCs) to power electrical drive system. DC/DC converters can be used for boosting or chopping the voltage level in electrical power flow. In this paper, a feedforward and feedback control circuit suitable for applications in the dc-dc pulse width modulated (PWM) boost converter operated in the continuous conduction mode (CCM) is proposed. DC/DC boost converter principle of operation is described and analyzed for steady state. The circuit is very simple and significantly improves line regulation of the output voltage.
DA/DA yükseltici Çeviricilerde geri besleme ve ileri besleme kontrol
National Conference on Electrical, Electronics and Biomedical Engineering (ELECO) -- DEC 01-03, 2016 -- Bursa, TURKEY